Respuesta :
Answer: Last Option
[tex]\frac{x^3}{x^5}=x^{-2}[/tex]
Step-by-step explanation:
We have the following expression:
x³ ÷ x⁵
This is:
[tex]\frac{x^3}{x^5}[/tex]
To simplify the expression, use the power division of the same base property
Remember that:
[tex]\frac{x^m}{x^n}=x^{m-n}[/tex]
Then we have that:
[tex]\frac{x^3}{x^5}=x^{3-5}[/tex]
↓
[tex]x^{3-5}=x^{-2}[/tex]
Finally:
[tex]\frac{x^3}{x^5}=x^{-2}[/tex]
The answer is the last option
Answer:
x^-2= 1/x^2
Step-by-step explanation:
x^3/x^5= x^(3-5)=x^(-2)= 1/x^2